Composição química do óleo essencial de sete genótipos de Lippia gracilis e reações de biotransformação de voláteis - Jesus, Hugo César Ramos de (2012)
This work attempts to make a study of the chemical composition of the essential oil from leaves of seven Lippia gracilis genotypes. In addition, we investigated the effect of water stress on the chemical composition of the essential oil (EO) of the species. A total of 32 volatile compounds were identified with predominance of phenolic monoterpenes: carvacrol, thymol and p-cymene. The seven genotypes were divided into two chemotypes: thymol chemotype, represented by the 106 genotype, and carvacrol chemotype, formed by the 107, 108, 109, 110, 201 and 202 genotypes. Biotransformation reactions have also been carried out using Botryosphaeria sp and Aspergillus niger as biocatalyst. In addition to the major components of the L. gracilis essential oil (carvacrol and thymol), the monoterpenes (+)-pulegone, geraniol, (-)-citronellol, (+)-limonene, rac-camphor and the two enantiomers of the fenchone were evaluated as substrates for biotransformation reactions. Botryosphaeria sp. catalyzed the hydroxylation of the camphor and fenchone at different positions, the carbon 6-endo of the camphor and the carbon 6-exo of the fenchone was the major site of addition of the OH group. Aspergilus niger catalyzed the hydroxylation of fenchone enantiomers and the isomerization of geraniol, resulting in formation of 6-exo-hidroxifenchone and of rac-linalool, respectively.